Procedures for chronic total occlusion: when are they recommended and when not. (18th November 2020) - Menozzi, Mila; Piovaccari, Giancarlo
Abstract: Coronary chronic total occlusion (CTO) produces an important clinical problem, often treated with medical therapy or coronary artery bypass grafting. Recent clinical studies, both registries and randomized trials, demonstrated that percutaneous coronary interventions (PCI), could provide a valid therapeutic option. Nonetheless, significant reduction in all-cause mortality, cardiac mortality, myocardial infarction, MACE, and MACCE has not been demonstrated in the subgroups analysis of randomized trials. These analyses suggest that PCI for CTO should be reserved for patients with angina or with large areas of the myocardium with reversible ischaemia. Large randomized studies should search for a personalized approach, considering the risks and complexity of PCI in CTO, which should mainly consider the extension of the ischaemia and the viability of the myocardium.